2019
DOI: 10.1038/s41598-018-36682-9
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid encapsulated into negatively charged liposomes exhibits increased skin permeation, retention and enhances collagen synthesis by fibroblasts

Abstract: Ascorbic acid (AA) is widely used in cosmetic formulations due to its antioxidant property and ability to increase collagen synthesis. Here, we encapsulated AA in vesicles with different lipid compositions. Negative liposome charge favored AA skin retention, with accumulation of 37 ± 12 and 74 ± 23 μg/cm2 in the epidermis and dermis, respectively, after 6 hours. Drug flux was influenced by the formulation composition, and both the presence of cholesterol and the liposomes surface charge were able to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 63 publications
1
57
0
1
Order By: Relevance
“…Our data evidenced in hDPSCs treated with 2 mM HEMA a decreased of cell viability starting from 24 up to 72 h, while the co-presence of AS was able to restored the proliferation rate in treated cells, this effect supports the strategic role of this antioxidant molecule in healing/regeneration process [64,65]. In fact, it has been demonstrated that AS promoted wound healing through matrix deposition, neo-vascularization and finally via secretion of inflammatory mediators [66].…”
Section: Discussionsupporting
confidence: 73%
“…Our data evidenced in hDPSCs treated with 2 mM HEMA a decreased of cell viability starting from 24 up to 72 h, while the co-presence of AS was able to restored the proliferation rate in treated cells, this effect supports the strategic role of this antioxidant molecule in healing/regeneration process [64,65]. In fact, it has been demonstrated that AS promoted wound healing through matrix deposition, neo-vascularization and finally via secretion of inflammatory mediators [66].…”
Section: Discussionsupporting
confidence: 73%
“…Searching for optimized formulation or delivery system is also important to enhance the permeation of the ingredients into skin. For example, ascorbic acid has limited application in the cosmetic field due to the unstable structure and low skin penetration [ 139 ]. The chemical modification of the hydroxyl group at the C-2 position of ascorbic acid produced stable derivatives such as 2-O-α-D glucopyranosyl-L-ascorbic acid (ascorbic acid 2-glucoside) [ 140 , 141 ].…”
Section: Application In Skin Rejuvenationmentioning
confidence: 99%
“…Ascorbic acid has many functions in the maintenance of various biological activities, including beneficial effects on skin, activity as cofactor in collagen biosynthesis, and antioxidant capacity. In particular, the molecules of ascorbic acid neutralize the free radicals present in the intra and extracellular matrices, avoiding damage to lipid membrane, DNA, and proteins that would be caused by oxidative stress (Maione-Silva et al, 2019). In medicine, its topical application guarantees anti-inflammatory and depigmenting effects (Farris, 2005;Stamford, 2012), while in the pharmaceutical sector ascorbic acid is mainly detected in pharmaceutical products for the quality assessment of, e.g., dietary supplements.…”
Section: Antioxidantsmentioning
confidence: 99%